2021
DOI: 10.1007/s00439-021-02338-4
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in diagnostic efficacy of comprehensive genetic testing for sensorineural hearing loss

Abstract: Understanding racial and ethnic disparities in diagnostic rates of genetic testing is critical for health equity. We sought to understand the extent and cause of racial and ethnic disparities in diagnostic efficacy of comprehensive genetic testing (CGT) for sensorineural hearing loss (SNHL). We performed a retrospective cohort study at two tertiary children’s hospitals on a diverse cohort of 240 consecutive pediatric patients (76% publicly insured, 82% non-White) with SNHL of unknown etiology who underwent CGT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 34 publications
2
29
1
Order By: Relevance
“…While CGT is one of the strongest tools in the clinical evaluation of SNHL, it must be equivalently accessible and informative across all populations, lest it exacerbate existing disparities. Several studies have found that Hispanic and Black populations are currently less served by genetic testing, with higher numbers of VUSs and poorer diagnostic rates (Yan et al 2016;Florentine et al 2021). In an attempt to understand and address the source of this disparity in genetic testing, we reviewed the distribution of studies on genetic testing in hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While CGT is one of the strongest tools in the clinical evaluation of SNHL, it must be equivalently accessible and informative across all populations, lest it exacerbate existing disparities. Several studies have found that Hispanic and Black populations are currently less served by genetic testing, with higher numbers of VUSs and poorer diagnostic rates (Yan et al 2016;Florentine et al 2021). In an attempt to understand and address the source of this disparity in genetic testing, we reviewed the distribution of studies on genetic testing in hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…This search identified studies in which either WES, multiple-gene testing (including CGT), or single-gene testing for common genes involved in hearing loss, excluding GJB2, was performed. We assembled this list of individual genes by examining a database of pediatric patients with SNHL who underwent CGT at UCSF (Florentine et al 2021). Each of the 41 genes included was possibly causative for hearing loss in two or more patients within a racially and ethnically diverse cohort.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…26 The diagnostic yield for HL gene panel testing has been reported to range from 12.7% to 64.3%. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] These rates have been based on research studies with largely homogenous study populations. Most had participants of European or East Asian origin; only 3 studies 28,39,41 included people of African origin.…”
Section: Introductionmentioning
confidence: 99%